Successful Implementation of Community Water - David E. Brumley, DDS, MPH; Rebecca W. Hawks, RDH, MPH; James A. Gillcrist, DDS, MPH; (Blackwell Synergy, 2000)
This paper describes the community diagnosis process and how it was used to implement community water fluoridation in Tennessee. Methods: Public health dental staff developed a survey instrument to collect communityspecific data on the oral health status of schoolchildren. Key survey findings were presented to county health councils who were determining and prioritizing the health needs of their communities